A lifetime prediction model for coated metallic bipolar plates in proton exchange membrane fuel cells. (1st March 2019) - Yi, Peiyun; Li, Xiaobo; Yao, Li; Fan, Fan; Peng, Linfa; Lai, Xinmin
Graphical abstract: Highlights: The model is used to predict the lifetime of coated metallic bipolar plates. The predicted results show good agreement with the experimental results. The model is universal and can be applied to metallic bipolar plates coated with different films. The model can provide theoretical guidance for the rapid development of coatings. Abstract: Metallic bipolar plates are considered to be cost-effective and feasible alternative to graphite bipolar plates for high power density of Proton Exchange Membrane Fuel Cells. However, the lifetime of metallic bipolar plates is determined by surface coating and the durability evaluation is extremely costly and time-consuming. It is urgent to establish a method for the lifetime evaluation and quick development of coated metallic bipolar plates. In this study, a lifetime prediction model for coated metallic bipolar plates is proposed and verified. Firstly, the model is established based on the electrochemical reaction kinetics of Proton Exchange Membrane Fuel Cells. Secondly, the operating conditions for automotive application are equivalent to the ex-situ accelerated tests for the coated metallic bipolar plates and the model is formulated based on the ex-situ accelerated tests. Finally, 2500 h in-situ test of stacks assembled with carbon-coated metallic bipolar plates is carried out to verify the accuracy of the model and the relative prediction error is 8.68%. The universality of the model has been evaluated by applying it to gold-coated metallic bipolar plates, which were tested in-situ in stacks up to 3000 h. This study is beneficial to the quick evaluation of lifetime for coated metallic bipolar plates and provides a theoretical guidance for the rapid development of coatings.